Analysis of a highly temperature-sensitive gold-coated plasmonic biosensor for analyte detection - Mohammad Rakibul Islam; Ehtesam Moazzam; Raisa Labiba Khan; Rakina Islam; Zarrin Tasnim (Ain Shams Engineering Journal, 2023)
A temperature-sensitive gold coated PCF-based surface plasmon resonance (SPR) biosensor was examined for detecting analytes based on their refractive indices. The proposed sensor attained maximum amplitude sensitivities (AS) of 1432 RIU−1 and 1291 RIU−1, wavelength sensitivities (WS) of 13,500 nm/RIU and 13,000 nm/RIU in X and Y- polarized mode individually in RI spectrum of 1.34–1.4. Furthermore, the proposed sensor produced ultimate figure of merit (FOM) values of 546.93 RIU−1 and 521.4601 RIU−1 in x and y polarization modes. High birefringence of 1.5 × 10−3 was also computed for the suggested sensor. Additionally, the proposed sensor shows high temperature sensitivity of 4.5833 nm/°C with a comparable resolution of 2.18××10−2 °C and a maximum FOM value of 0.101 °C−1 in the detection range of −114 °C to 78 °C in the presence of ethanol as a sensing medium. The reported sensor therefore can be considered as a notable solution for any chemical or biological analytes detection.